ZEN: a directive based experiment specification language for performance and parameter studies of parallel scientific applications. (11th November 2005) - Prodan, Radu; Fahringer, Thomas
Currently there exists little support to specify and control the execution of a large number of experiments required for performance oriented development of scientific applications. We have developed a new directive based language called ZEN for the specification of wide sets of synthetic experiments in the context of large scale parameter and performance studies of parallel applications. We report experimental results for the performance analysis of an ocean simulation application and for the parameter study of a computational finance code.